PROTOTYPE LAMPU LALU LINTAS ADAPTIF BERBASIS MULTI AGENT MANGGUNAKAN LOGIKA FUZZY YANG TERTANAM PADA MICROCONTROLLER - Adrin T; Heribertus Himawan; Suprapedi Suprapedi (Jurnal Teknologi Informasi - Cyberku (JTIC), 2017)
Traffic light is a very important tool for urban life in regulating the smooth flow of traffic on the highway. The use of traffic lights are now much more applied using static timing system or a traffic light system which does not know the condition of the crossing are many vehicles or fewer. Timing pattern that is applied from one segment to another segment is set in rotation. In the study conducted to design a traffic light prototype based on multi- agent using fuzzy logic which is planted on the microcontroller. There are two parts and types of microcontrollers are used to design the prototype. The first part, the Slave microcontroller Atmega 32 and the second type, the type of Master mikontroler Atmega 128. Traffic light system which can adapt to the environment made the crossing. If there is a deviation of the queue of vehicles which have very much, then the green light time longer than the deviation that only have a little queue of vehicles. Thus, the traffic light is more adaptive to the dynamic vehicle that will cross the intersection. Traffic lights can also communicate with traffic lights nearest neighbors in both directions. Communication is done through mutual give information about the number of vehicles that left deviation towards each junction nearest neighbors. Results of this study found that the performance of fuzzy logic embedded in the microcontroller can control traffic lights with dynamic adaptive to existing vehicles on Line 1, Line 2 and Line 3. Prototype designed traffic lights represent the environmental conditions that have multiple intersections and each intersection has four traffic lights that can communicate with Multi Agent another intersection nearest neighbors.